Trace element deficiencies in Red Yellow Podzolic soil and their correction with pellets of fritted trace elements (F.T.E.) - De-Polli, Helvécio; Döbereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
Three greenhouse experiments were conducted with a Red Yellow Podzolic soil (pH 5.1) that commonly occurs on the steep hills used for pastures in the state of Rio de Janeiro. The purposes of the study were to observe the effects of F.T.E. on the growth of four species of tropical legumes and the symbiotic fixation of nitrogen. Plant response to four different F.T.E. formulations was measured in terms of root nodule numbers and weight, plant dry matter production, and total N content. From the differencial effects of the 4 F.T.E. formulae it was deducted that Mn or Fe were suspect as being limiting in the legume - Rhizobium symbiosis, although other micronutrients may also have been involved. Plant responses to applications of a F.T.E. containing all micronutrients. Crude protein production by Centrosema pubescens, Phaseolus atropurpureus, Glycine wightii, and Stylosanthes guyanensis, was doubled by these treatments. Except in the case of Stylosanthes guyanensis, similar increases in crude protein when the F.T.E. formulations were applied as pellets consisting of various combinations of F.T.E., lime, rock phosphate, and peat inoculum. Increases in legume dry matter production were less than those in crude protein content, but still highly significant. Applications of F.T.E. in pellets initially induced chlorosis in the legume seedlings. The chlorosis was almost completely eliminated by pelleting with F.T.E. mixed with lime or by layering the pellets with F.T.E. and lime. In culture medium, Rhizobium was not inhibited by any of the four F.T.E. formulations.